Momordica charantia seed oil methyl esters: a kinetic study and fuel properties - Rashid, Umer; Ahmad, Junaid; Yunus, Robiah; Ibrahim, Muhammad; Masood, Hassan; Muhammad Syam, Azhari (Taylor & Francis Inc., 2014)
Due to growing concerns such as increasing energy demand and the environmental issues-related fossil energy problems caused by consumption of fossil energy, it is needed to focus on nonedible oils for biodiesel production. In the present research work, the seed oil of Momordica charantia (M. charantia) was for the first time appraised as possible nonedible oil for synthesis of biodiesel. M. charantia has oil content (36.10 ± 4.20%), high acid value (1.82 mg KOH g−1), and its oil enable base-catalyzed transesterified for biodiesel production after acid pretreatment. It was transesterified under standard conditions at 6:1 molar ratio of methanol to oil; sodium methoxide (1.00 wt.% in relation to oil mass) as a catalyst; 60°C reaction temperature and 90 min of reaction time. At optimum conditions biodiesel yield of 93.2% was acquired. The reaction followed first order kinetics. The activation energy (E A) was 254.5 kcal mol−1 and the rate constant value was 1.30 × 10−4 min−1 at 60°C. Gas chromatography investigation of M. charantia seed oil methyl esters (MSOMEs) depicted that the fatty acid composition comprises a high proportion of mono-unsaturated fatty acids (64.11 ± 5.02%). MSOMEs were also characterized using Fourier Transform Infrared and 1H Nuclear Magnetic Resonance spectroscopy. The tested fuel properties of the MSOMEs, except oxidative stability, were conformed to EN 14214 and ASTM D6751 standards. The low-value oxidative stability of MSOMEs can be solved by adding antioxidants additives. In summary, M. charantia oil has potential as nonedible raw material for biodiesel production.